FRAMING THE TURKMENBASHI: ESTERN PRESS PORTRAYALS OF THE LATE PRESIDENT OF TURKMENISTAN - FREEDMAN, Eric (CENTRAL ASIA AND THE CAUCASUS, 2007)
Studies have found that U.S. and other Western news media now devote less newspaper space, airtime, and financial and staff resources than in the past to foreign news, particularly news unrelated to ongoing wars in which the United States is engaged. That means more competition among “foreign” stories to get into print or onto the air, with editors and news directors exercising their professional judgment in selecting among competing offerings. With novelty among the widely accepted standard news values, it is no surprise that a story about a quirky foreign ruler such as the late president of Turkmenistan, or unusual law or governmental policy may edge out more “serious” stories in that competition for attention. Turkmen President Saparmurat Niyazov, who died on 21 December, 2006, clearly fit the definition of a quirky, idiosyncratic, and authoritarian ruler. This study examines how three Western news organizations framed Niyazov during a one-year period and how they reported to their readers and audiences about Turkmenistan, specifically the prevalence of personal references to, and personalizing terminology about, the self-described “Turkmenbashi.” Finally, it discusses the implications of such media framing for Western understanding of Turkmenistan and its issues, and the consequence that readers lose the opportunity to become informed about serious public policy issues that may directly or indirectly affect them and their own country in such matters as economics, security, politics, human rights, public health, energy, the environment, development, and religious and cultural movements.